The translanguaging pedagogy as an approach for teaching English in rural schools - Ramirez, Óscar Mauricio (Technium Social Sciences Journal, 2025)
This article discusses the benefits of translanguaging pedagogy in teaching foreign languages, particularly in Colombian rural schools. Translanguaging aims to generate confidence in learners, break down barriers, and reduce learning gaps in rural contexts. The research provides a characterization of the teaching task, epistemological reflection, and cognitive development in students, generating possibilities for applying translanguaging in learning English. The proposal is based on low Saber tests, which show that 87% of students in rural areas have low levels compared to 70% in urban schools. The study uses a qualitative research paradigm with a population sample of fifth and seventh graders, teaching translanguaging using the Integrated Learning of Contents and Foreign Languages (CLIL) methodology. The results show that translanguaging is an excellent option for supporting the learning of a second language in the classroom, as the linguistic resources used cannot be discarded.